2013
DOI: 10.1007/s00705-013-1692-9
|View full text |Cite
|
Sign up to set email alerts
|

Innate and adaptive immune responses in patients with pandemic influenza A(H1N1)pdm09

Abstract: Innate and adaptive immune responses play critical roles in the body's defense against viruses. We investigated the host immune response against the 2009 pandemic H1N1 influenza virus [A(H1N1)pdm09] in patients before and after anti-influenza therapy and found that the numbers of dendritic cells and T cells were significantly reduced compared with those of a healthy control group. In contrast, the frequency of natural killer, cdT and T regulatory (T reg ) cells increased, and the concentrations of plasma inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…Even though these studies looked at different compartments (i.e. peripheral blood versus pulmonary), they also observed an increase in the frequency of Tregs in infected patients that correlated with decreased frequencies of CD3 + , CD4 + and CD8 + T cells [37]. And in a separate study, elevated levels of IL10 in sera were positively correlated to severity of disease in patients infected with pH1N1 [38].…”
Section: Discussionmentioning
confidence: 99%
“…Even though these studies looked at different compartments (i.e. peripheral blood versus pulmonary), they also observed an increase in the frequency of Tregs in infected patients that correlated with decreased frequencies of CD3 + , CD4 + and CD8 + T cells [37]. And in a separate study, elevated levels of IL10 in sera were positively correlated to severity of disease in patients infected with pH1N1 [38].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have observed an increased number of mDCs and pDCs in the nasal mucosa, but a decreased number in the peripheral blood of influenza virus-infected patients (Gill et al 2005 , 2008 ; Huang et al 2013 ), supporting the recruitment of circulating DCs to the site of infection. Furthermore, influenza virus infection induced activation of human DC subsets including CD1c + mDC1, pDC and moDCs characterized by upregulation of expression of HLA-DR, HLA-ABC, CD80, CD86, CD40, and CCR7 (Fonteneau et al 2003 ; Larsson et al 2000 ; le Nouen et al 2011 ; Osterlund et al 2005 ; Piqueras et al 2006 ; Smed-Sorensen et al 2012 ).…”
Section: Cells Of the Innate Immune System Involved In Immunity To Inmentioning
confidence: 95%
“…[8,[13][14][15] . [8,[18][19][20][21][22] . Virtually all arms of the immune system may be antagonized by viruses, including innate immunity and both types of adaptive immunity (humoral and cell-mediated).…”
Section: All Infected Patients Have a Detectable B-cell Responsementioning
confidence: 99%
“…Apoptosis may be triggered by a range of mechanisms. Interferon, paradoxically, is well-known for induction of immunopathology, both acutely and on chronic exposure[5,21,42] . Acute interferonopathies result from upregulation of death receptors and apoptosis-inducing ligands on monocytes, airway epithelial cells, and lymphocytes, while chronic type I interferonopathy results from induction of immunosuppressive cytokines like IL-10 and overexpression of PD-1 and PDL-1.…”
mentioning
confidence: 99%
See 1 more Smart Citation